Compression of frequency-swept microwave pulses using a helically corrugated waveguide - Cross, A; Machines, P; Samsonov, S; Phelps, A; Burt, G; Ronald, K; Bratman, V; Denisov, G; Young, A; Whyte, C; He, W; Konoplev, I; et al. (2005)
Microwave pulse compression is an important area of research in vacuum electronics, with important applications for linear accelerators, RADAR and non-linear testing. The principles and methods of pulse compression differ greatly depending on the application. The concept of producing ultra-high-power nanosecond microwave pulses, using passive sweep-frequency compression, was studied. A novel waveguide with a helical corrugation of its inner surface was used as the microwave pulse compressor. This structure couples a TE11 traveling wave with a near cut-off TE21 wave producing a region far from cut-off with a large change in group velocity with frequency. A 2.08 meter long copper helical waveguide was used to compress a 67ns, 5.7kW frequency-swept pulse from a high power TWT, driven by a swept solid-state source, to a 2.8ns 68kW pulse containing ∼50% of the energy of the input pulse. The dispersion characteristics of the helically corrugated waveguide was investigated both experimentally and theoretically. A vector network analyser was used to measure experimentally the dispersion characteristics of complex waveguides and the code MAGIC was used to calculate the dispersion theoretically. Good agreement between experimental results and theoretical predictions was observed. © 2005 IEEE.